Theory of the Earth, With Proofs and Illustrations, Volume 1 (of 4) - Hutton, James, 1726-1797 (Salt Lake City, UT : Project Gutenberg, 2004)
"Theory of the Earth, With Proofs and Illustrations, Volume 1 (of 4)" by James Hutton is a geological work published in 1795. This groundbreaking publication laid the foundations for modern geology by demonstrating that Earth results from natural forces operating over immense time spans. Hutton proposed that observable processes today, given enough time, could explain the geological features we see in rocks. His work challenged biblical timelines and introduced uniformitarianism, profoundly influencing later scientists including Charles Lyell and Charles Darwin. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Theory_of_the_Earth
Release date is 2004-07-09
E-text prepared by Robert Shimmin, Renald Levesque, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Geology -- Early works to 1800